ADVANCE-1: An adapted collaborative benchmarking approach in centre-based lung cancer care. (January 2021) - McCann, Brendan; Muhr, Riccardo; O'Rourke, Noelle; Milroy, Robert; Kollmeier, Jens; Misch, Daniel; van der Horst, Joris; Morrison, David; Bauer, Torsten; Massalski, Oliver; Blum, Torsten Gerriet
Highlights: Benchmarking is used by industry to improve structure, processes, and outcomes. Benchmarking can equally be used by lung cancer services. Creation of a benchmarking tool and its application in two lung cancer services for comparison. Comparison of lung cancer services and their cancer registries using benchmarking tool. Establish best practice points and learn from each other. Abstract: The majority of research within lung cancer is focused on prevention, diagnosis and treatment rather than examining infrastructure or processes of lung cancer centres. Benchmarking is a systematic method for documenting and comparing processes, functions or performance of organisations against the best in the world. ADVANCE-1 is a European Respiratory Society funded pilot study with the main aim of creating a benchmarking tool that can easily document and reflect the structure and process within a lung cancer centre and its associated registry. By doing this we can then compare centres and generate best practice learning points from each centre in order to learn from each other. The ADVANCE-1 study group was constituted by two ERS fellowship-holders and senior lung cancer specialists from the two participating lung cancer services in Glasgow, Scotland, and Berlin, Germany. The study design and benchmarking tools were reviewed externally. Once the benchmarking tools were created, prospective testing was undertaken in the two participating centres in order to allow comparison to ascertain best practice in a so called 'collaborative benchmarking approach'. We were then able to create personalised learning points for each centre. The next phase of the project will be to expand the benchmarking across several European centres in the ADANCE-2 project.